2015
DOI: 10.1108/jhom-03-2014-0048
|View full text |Cite
|
Sign up to set email alerts
|

Managing processes of inpatient care and treatment

Abstract: This study contributes qualitative descriptions of leadership characteristics and the prerequisites necessary for active process management in the context of managing processes of inpatient care and treatment at Swedish hospitals, a subject that has not been investigated earlier.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…When implementing process-oriented management strategies it has been found important to clarify process managers’ responsibility and work content [ 21 ]. Furthermore it was important to emphasize process managers’ basic requirements in order to do a good job [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…When implementing process-oriented management strategies it has been found important to clarify process managers’ responsibility and work content [ 21 ]. Furthermore it was important to emphasize process managers’ basic requirements in order to do a good job [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…The case studied here is such an example, as are many health-care organizations. For example, studies of process leaders (Nilsson and Sandoff, 2015a, 2015b) working in health-care organizations showed that process leaders experienced problems in leading processes “against the grain” in a hierarchical organization in which authorization to make decisions followed the hierarchical order.…”
Section: Discussionmentioning
confidence: 99%
“…An explorative and qualitative approach (Patton, 2002) was used in the study with individual interviews as the data collection method because the aim was to grasp the experiences of the development leaders participating; qualitative methods have been recommended to obtain knowledge and understanding about the meaning people invest in specific situations or phenomena, such as development leaders’ experiences of working in teams. Similar design and methods have been used in several other studies (Nilsson et al , 2005, 2007; Nilsson and Sandoff, 2015a, 2015b; Sandoff and Widell, 2015; Bååthe et al , 2016).…”
Section: Methodsmentioning
confidence: 99%
“…Organizational learning, knowledge management and transformational leadership have been found to exercise positive reciprocal influence on each other, thus facilitating organizational innovation (Noruzy et al , 2013). The importance of a holistic management perspective has been highlighted when implementing process-oriented approaches in healthcare and integrating leadership competences and prerequisites such as structure, time and information (Nilsson and Sandoff, 2015b). A work environment where integrated learning activities are interwoven makes it easier for employees to experience manageability, comprehensiveness and meaningfulness at work.…”
Section: Introductionmentioning
confidence: 99%